Development of a Novel Pneumatic Oscillator for the Tissue Paper Industry - Michele Gabrio Antonelli (MDPI AG, 2021)
The final quality of tissue paper depends on the parameters of the continuous transformation process and maintenance of rolls of a tissue paper machine. For a better quality, outer surfaces of the rolls must always be clean, and their roughness should be maintained in the same way. A Doctor Blade provides for such requirements. Our work is focused on the development of a pneumatic oscillator that moves a Doctor Blade in order to scrape the outer surfaces of the rolls. It is based on a low-friction double-effect cylinder with a through-rod. The integration of two limit switch valves, one for each head of the cylinder, and a smart pneumatic circuit to obtain a very low speed of the piston at constant load, represents the novelty of the proposed device. The piston of the cylinder allows for alternatively switching the limit switches that command the 5/2 air-operated pilot valve of the cylinder. The oscillator’s design, pneumatic circuit, and working principle are detailed. Experimental tests on the conceived limit switch and on the first prototype of the pneumatic oscillator validated the effectiveness of the proposed solution, the technical feasibility of the device, and the absence of stick-slip during the oscillatory motion at low speed.